A Blockchain Based Online Voting System Using Ethereum - M. S., Priya; Jose, Sangeetha; Joseph, Jino (Indian Journal of Computer Science, 2025)
Online voting with blockchain technology is a decentralised and secure live-voting system which can be implemented using an Ethereum blockchain. Our proposed blockchain-based voting system (BVote) uses the Ethereum blockchain technology to overcome the issues of the existing voting system, such as vote tampering, double voting, and hacking. Our system offers several benefits including increased security, transparency, and immutability. The immutability of blockchain ensures that once a vote is recorded, it cannot be altered or deleted, thereby enhancing the integrity of the election process. Additionally, voting and counting occur simultaneously, thereby providing partial results. Double voting is addressed using a unique digital identity for each voter that is verified in the blockchain network. To authenticate the user identity, each transaction should be digitally signed using a private key. This ensures that only voters can access and use their digital identity to cast a vote. To ensure the privacy of the voter, the data are hashed using a Secure Hash Algorithm. To ensure the anonymity of the voter, the vote is encrypted to break the link between voter and their vote. This helps to protect voters’ privacy and prevents attempts to trace their votes. By utilising the Elliptic Curve Digital Signature Algorithm, a digital signature is generated for each transaction that occurs during the voting process. This ensures the authenticity of the data stored on the blockchain and prevents any unauthorised modifications or tampering of the data, which further improves security.